Loading of Iron (II, III) Oxide Nanoparticles in Cryogels Based on Microfibrillar Cellulose for Heavy Metal Ion Separation - Jinhua Yan; Huanlei Yang; Juliana C. da Silva; Orlando J. Rojas (Advances in Polymer Technology)
Cryogels based on microfibrillar cellulose (MFC) and reinforced with chitosan to endow water resistance were loaded with magnetite nanoparticles (MNPs) and characterized by TEM, XRD, and TGA. The MNP-loaded cryogels were tested for heavy metal ion removal from aqueous matrices. The adsorption capacity under equilibrium conditions for Cr(VI), Pd(II), Cd(II), and Zn(II) was measured to be 2755, 2155, 3015, and 4100 mg/g, respectively. The results indicate the potential of the introduced bicomponent cryogels for nanoparticle loading, leading to a remarkably high metal ion sorption capacity.